Isolation and molecular characterization of Cordyceps sp. from Bemisia tabaci (Hemiptera: Aleyrodidae) and pathogenic to Glycaspis brimblecombei (Hemiptera: Aphalaridae) - Domingues, M. M. [UNESP]; Santos, P. L. [UNESP]; Gêa, B. C. C. [UNESP]; Carvalho, V. R. [UNESP]; Oliveira, F. N. [UNESP]; Soliman, E. P.; Silva, W. M.; Zanuncio, J. C.; Santos, V. C.; Wilcken, C. F. [UNESP] (Instituto Internacional de Ecologia, 2022)
The Brazilian forestry sector stands out for its technology, forestry management practices, social and environmental responsibility and, mainly, for its high productivity and exotic pests can reduce it. The red gum lerp psyllid Glycaspis brimblecombei (Moore, 1964) (Hemiptera: Aphalaridae) is an important pest in Eucalyptus plantations. The parasitoid Psyllaephagus bliteus (Riek, 1962) (Hymenoptera: Encyrtidae), predatory bugs and entomopathogenic fungi such as Beauveria bassiana and Metarhizium anisopliae are the natural enemies and used in the biological control of the red gum lerp psyllid. The use of entomopathogenic fungi against exotic pests is increasing in the forestry sector and the prospecting and identification of fungus isolates is important for integrated pest management. The objective of this work was the isolation and molecular identification of Cordyceps spp. And to evaluate the pathogenicity of isolates, obtained from Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) adults, against to the red gum lerp psyllid G. brimblecombei. The fungi were isolated from B. tabaci adults found in soybean and tomato crops and molecularly identified. The conidia obtained were suspended in solution with Tween 80 (0.1%) at a concentration of 1.0 × 108 conidia/mL and sprayed on ten G. brimblecombei nymphs per Eucalyptus leaf cut and placed on a hydroretentive gel inside per Petri dishes as a replication. The number of dead insects was quantified, daily, for seven days, and transferred to humid chambers. Cordyceps javanica (LCBPF 11) and C. fumosorosea (LCBPF 12 and LCBPF 63) were identified with a molecular analysis and all isolates were pathogenic to the insects and indicates that they could be used to manage G. brimblecombei and adds to reports that, normally, fungi cause greater mortality on insects of the same order as that from which they were isolated.

O setor florestal brasileiro se destaca pela tecnologia, práticas de manejo florestal, responsabilidade social e ambiental e, principalmente, alta produtividade, mas pragas exóticas podem reduzir isto. O parasitoide Psyllaephagus bliteus (Riek, 1962) (Hymenoptera: Encyrtidae), percevejos predadores e fungos entomopatogênicos como Beauveria bassiana e Metarhizium anisopliae são inimigos naturais usados no controle biológico do psilídeo-de-concha do eucalipto Glycaspis brimblecombei (Moore, 1964) (Hemiptera: Aphalaridae), praga em plantios de eucalipto. A utilização de fungos entomopatogênicos contra pragas exóticas vem aumentando no setor florestal e a prospecção e identificação de isolados fúngicos é importante para o manejo integrado de pragas. O objetivo deste estudo foi o isolamento e identificação molecular de Cordyceps spp. e avaliar a patogenicidade dos isolados de Cordyceps javanica (LCBPF 11) e Cordyceps fumosorosea (LCBPF 12 e LCBPF 63), obtidos de adultos de Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae), ao psilídeo-de-concha G. brimblecombei. Os fungos foram isolados de adultos de B. tabaci encontrados em culturas de soja e tomate e identificados molecularmente. Os conídios foram suspensos em solução com Tween 80 (0,1%) na concentração de 1,0 x 108 conídios/mL e pulverizados sobre dez ninfas de G. brimblecombei por folha de Eucalyptus cortada e colocada sobre gel hidrorretentor no interior de placas de Petri por repetição. O número de insetos mortos foi quantificado, diariamente, por sete dias e transferidos para câmaras úmidas. Cordyceps javanica (LCBPF 11) e C. fumosorosea (LCBPF 12 e LCBPF 63) foram identificados por análise molecular e todos os isolados foram patogênicos para os insetos. Isto indica serem importantes para o manejo de G. brimblecombei e confirma relatos de que, normalmente, fungos causam maiores mortalidades em insetos da mesma ordem daquela da qual foram isolados.
Isolamento e caracterização molecular de Cordyceps sp. de Bemisia tabaci e patogênico para Glycaspis brimblecombei (Hemiptera: Aphalaridae)
Keywords: biological control; Cordyceps fumosorosea; Cordyceps javanica; entomopathogenic fungi; Eucalyptus; controle biológico; Cordyceps fumosorosea; Cordyceps javanica; fungos entomopatogênicos; Eucalyptus